Spiritual comfort, spiritual support, and spiritual care: a simultaneous concept analysis - Tavares, Ana Patrícia (2022)
Background: Spirituality is a dimension of life and the human being that should be included in holistic healthcare. One major barrier often described by nurses on implementing spirituality in practice relates to perceiving the concept of spirituality as subjective and sharing confounding similarities with other concepts. In this sense, the concepts of spiritual comfort, spiritual care, and spiritual support may require more distinct theoretical definitions aimed at clear and effective nursing interventions within spiritual care. Aim: To provide a definition of spiritual comfort, spiritual support, and spiritual care. Methods: Simultaneous concept analysis (SCA) of three concepts according to Haase et al., which is grounded on Rodgers' evolutionary view. The method was based on a literature review with the search of electronic databases on May 2020. Search and analysis have been blinded conducted by two reviewers. Results: One hundred thirty-six studies were included in the SCA. Findings suggest that spiritual comfort is an immediate state and an outcome. Spiritual support is related with an intimate and positive relationship with God. Spiritual care is defined as a complex and interactive process. Both spiritual support and spiritual care are grounded in a therapeutic context. Conclusion: This SCA allowed the attributes of each concept to be identified and provides definitions that may facilitate the understanding of these concepts and promote the implementation of spirituality in nursing practice, but which has also led to future research on this topic.